Reducing blood uric acid levels after drinking Annona muricata linn (soursop leaf) extract: study in elderly with hyperuricemia - Muhammad Al Amin; Ainun Najib; Ali Syahbana; Efina Amanda (PROFESSIONAL HEALTH JOURNAL, 2024)
Introduction: Gout is a degenerative disease that often attacks joints, especially in older adults. This disease is caused by the buildup of uric acid crystals in the joints, which causes inflammation and severe pain. One of the main indications that someone suffers from gout is if the results of measuring the uric acid level in the blood are more than 7.0 (mg/dL), whereas in women, it is more than 5.7 mg/dL. Objectives: Research to determine the effectiveness of A. Muricata leaf extract in reducing uric acid levels in older adults with hyperuricemia. Methods: Quantitative research, using a quasi-experimental type with Pre-test, Post-test design with control group design, with a sample size of 30 older adults, sampling technique using random sampling carried out for one week consuming one day three times. Results: The paired t-test showed a p-value of 0.0001, indicating a significant difference between the average uric acid levels before and after Annona muricata leaf extract administration. Soursop leaves contain flavonoid and tannin compounds, where flavonoids can inhibit the production of the enzyme xanthine oxidase. By inhibiting this enzyme, the process of forming hypoxanthine into xanthine is also hampered, thereby reducing excess uric acid production. Apart from reducing uric acid levels in the blood, soursop leaves can also reduce pain in people with gouty arthritis thanks to the tannin, resin and Agostini content, which can relieve pain and reduce swelling and pain. Conclusions: Administration of A. Muricata leaf extract has proven effective in reducing uric acid levels in older adults with hyperuricemia